Does Autopulse Mechanical Chest Compression Improve Outcomes After Cardiac Arrest? A systemic review and meta-analysis - Qasem Ahmed Almulihi; Asaad Suliman Shujaa; Bader Jameel Aldossary; Mohammad Ibrahim Faya Assiri; Abdullah Ahmed T Al Bahrani; Shahd Ali Al Rashed; Fawaz Hassan Alali; Abdullah Ali Alaithan; Ghanem Mohammed Aldubayyan; Mohammed Ali Alaithan; Hussain Ali AlBakhite; Yaser Mohammed Hussain Alsultan; et al. (Saudi Journal of Emergency Medicine)
Background: Cardiac arrest remains a critical global health challenge, necessitating effective interventions to improve outcomes. Autopulse Mechanical Chest Compression has emerged as a potential adjunct to conventional manual cardiopulmonary resuscitation (CPR). This study aimed to comprehensively investigate the association between Autopulse use and various outcomes following cardiac arrest. Methods: A thorough literature review was conducted using PubMed, Embase, Scopus, Google Scholar, CINAHL, and the Cochrane Library. Articles were evaluated for eligibility according to predefined criteria. The collected data was synthesized, and the findings were subsequently presented. Results: Sixteen studies were included in the study. A synthesis of diverse studies revealed nuanced perspectives on Autopulse Mechanical Chest Compression. Enhanced CPR success and improved survival rates in out-of-hospital cardiac arrest were demonstrated, while potential drawbacks were suggested, warranting scrutiny of device design and implementation strategies. Meta-analyses on ROSC favored Autopulse, indicating a statistically significant advantage over Manual CPR (relative risk 1.43, 95% CI 1.07-1.92). Complication analyses showed no significant difference (relative risk 1.11, 95% CI 0.93-1.33), emphasizing comparable safety profiles. Patient survival rates exhibited variations, with Autopulse demonstrating higher rates in some studies, but nuances were observed in 30-day survival and hospital discharge rates. Conclusion: Autopulse Mechanical Chest Compression holds promise as a supplementary strategy in cardiac arrest resuscitation. However, complexities arose in longer-term outcomes, highlighting the need for contextual considerations. [SJEMed 2024; 5(1.000): 030-041]